A study of the effects of fear of Covid-19, locus of control, and gender on depression among undergraduates in Malaysia - H’ng, Zhuang Hang; Wong, Ker Yin; Yau, Chiow Yee (2021)
Suicide cases in Malaysia surged during the Covid-19 pandemic and depression remains ahuge yet undiscovered cause to this situation, especially among the undergraduate’spopulation. This study aims to identify the effects of fear of Covid-19 and locus of control ondepression, as well as to explore the gender differences in depression among undergraduatesin Malaysia. Using a cross-sectional survey design, the purposive sampling method wasapplied to recruit undergraduate respondents from universities and colleges in the entireMalaysia. A total of 343 participants were recruited through online communication platformsand 307 were retained for final analyses. The Fear of Covid-19 Scale (FCV-19S), Levenson’sMultidimensional Locus of Control Scale, and Beck’s Depression Inventory-II (BDI-II) wereutilized for data collection. All 307 participants were 18 to 25 years old, with 55.6% femalesand 85% Chinese undergraduates. Findings revealed that fear of Covid-19 and all threedimensions of locus of control were associated with depression. However, only internal locusof control and external locus of control (chance) significantly predicted depression. Besides,no significant difference in depression was found in the sample. In short, the current studyrevealed new insights to the literature of depression in the Malaysia context, shed light onpotential ways of addressing depression among undergraduates, and set the foundation forfuture research to explore different protective factors that can buffer the effects of Covid-19pandemic on depression.